The Angle of Progression at Station 0 and in Magnetic Resonance and Transperineal Ultrasound Assessment - Iliescu, D. (Case Rep Obstet Gynecol, 2015)
The transperineal ultrasound (TPU) value of the angle of progression (AOP) during fetal head engagement, at station 0, is a critical cut-off for current obstetrical practice, especially when intrapartum instrumental interventions are required. Still, controversial measurements were reported in previous high resolution imagistic studies. Our TPU and direct “gold-standard” magnetic resonance (MRI) measurements confirm that station 0 corresponds to a 120° AOP, concordantly. Based on these findings, the fact that an AOP of 120° or greater was previously strongly associated with vaginal delivery may be due to the achievement of head engagement in labor.